Studies of Modification of Zeolite by Tandem Acid-Base Treatments and its Adsorptions Performance Towards Thorium - G. Nurliati; Y.K. Krisnandi; R. Sihombing; Z. Salimin (PPIKSN-BATAN, 2015)
Hierarchical zeolite was prepared from natural zeolite using tandem acid-base treatments and applied as adsorbent for Th(IV) removal. Natural zeolite occurred naturally as microporous material. It was modified using two familiar methods simultaneously, dealumination and desilication techniques, to change its micropore size into hierarchical pores.. Extensive characterization of both natural and modified zeolites were conducted using XRD, BET, SEM-EDS, and AAS. XRD Patterns of raw, pre-treated , and acid-base tandem modified zeolites show that the modification process has not changed the crystal properties of this material. However, the Si/Al ratio is increased from 6.688 to 11.401 for Na-zeolite (NaZ) and modified zeolite, ZA2B respectively. The surface area is increased from 125.4 m2/g (NaZ) to 216.8 m2/g (ZA2B), indicative of the creation of mesopore in addition to naturally micropore structure. The application of these zeolite materials as adsorbent were carried out using solution of 50 ppm Th4+measured using UV-Vis spectrophotometer. The UV-Vis result shows that the modified zeolite (ca. 10 mg) has higher adsorption capacity than natural zeolite. The adsorption process does not fit into Langmuir and Freundlich isotherm and the adsorption capacity of this material increase from 909 mg/g to 2000 mg/g for NaZ and ZA2B respectively.Received: 26 January 2015; Revised: 20 May 2015: Accepted 21 May 2015